IMPLEMENTASI KEBIJAKAN PENGELOLAAN KEUANGAN BADAN LAYANAN UMUM DAERAH (BLUD) DI UPT. RUMAH SAKIT UMUM MOKOYURLI BUOL - Mahmud, Syamsiar I. (STISIPOL Mujahidin Buol, 2024)
The implementation of the management of the Regional Public Service Agency (BLUD) at Mokoyurli Buol Hospital is an effort to improve the efficiency, effectiveness, and quality of health services provided by the hospital. The purpose of this study was to determine and describe: Implementation of the financial management policy of the Regional Public Service Agency at UPT. Mokoyurli Buol General Hospital, using the Charles O Jones implementation model. The research method used is qualitative descriptive, the location of the study was carried out at Mokoyurli Buol Hospital, Buol Regency. Data collection techniques in the form of observation, interviews and documentation which were then analyzed using qualitative data based on the concepts of Miles and Huberman. The results of the study indicate that the implementation of BLUD management at Mokoyurli Regional Hospital, Buol Regency has been carried out but has not been optimal because there are several challenges faced, namely the organizational structure of BLUD at Mokoyurli Regional Hospital, Buol does not fully support the flexibility and responsiveness needed in BLUD management, there are still limited understanding and capacity of human resources (HR) related to the BLUD concept, and financial management at Mokoyurli Regional Hospital, Buol is still carried out manually, which results in inefficiency in recording, reporting, and financial decision making.